Basic PKP-PK Initial Training Sebagai Sarana Peningkatan Pelayanan Gawat Darurat di Bandar Udara - Wildan Nugraha; Anton Abdullah; Sutiyo Sutiyo; Oke Hendra; Iraldy Julian Marwan (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
Aircraft Rescue and Firefighting (ARFF) is a part of the emergency response unit at the airport that has technical and operational standards set by the regulator. Given the importance of the role of ARFF in an airport, it is appropriate for ARFF unit to have competent personnel in their fields. This can be obtained through education and training organized by the Aviation Education Institute. One of the Basic ARFF training programs by Poltekbang Palembang overall went well and smoothly, with an average score of 83.46 (qualification: excellent) can be an indicator that the learning objectives have been achieved.